Characterisation of worldwide Helicobacter pylori strains reveals genetic conservation and essentiality of serine protease HtrA. Issue 5 (22nd December 2015) - Tegtmeyer, Nicole; Moodley, Yoshan; Yamaoka, Yoshio; Pernitzsch, Sandy Ramona; Schmidt, Vanessa; Traverso, Francisco Rivas; Schmidt, Thomas P.; Rad, Roland; Yeoh, Khay Guan; Bow, Ho; Torres, Javier; Gerhard, Markus; et al.
Summary: HtrA proteases and chaperones exhibit important roles in periplasmic protein quality control and stress responses. The genetic inactivation of htrA has been described for many bacterial pathogens. However, in some cases such as the gastric pathogen H elicobacter pylori, HtrA is secreted where it cleaves the tumour‐suppressor E‐cadherin interfering with gastric disease development, but the generation of htrA mutants is still lacking. Here, we show that the htrA gene locus is highly conserved in worldwide strains. HtrA presence was confirmed in 992 H . pylori isolates in gastric biopsy material from infected patients. Differential RNA‐sequencing (dRNA‐seq) indicated that htrA is encoded in an operon with two subsequent genes, HP1020 and HP1021. Genetic mutagenesis and complementation studies revealed that HP1020 and HP1021, but not htrA, can be mutated. In addition, we demonstrate that suppression of HtrA proteolytic activity with a newly developed inhibitor is sufficient to effectively kill H . pylori, but not other bacteria. We show that H elicobacter   htrA is an essential bifunctional gene with crucial intracellular and extracellular functions. Thus, we describe here the first microbe in which htrA is an indispensable gene, a situation unique in the bacterial kingdom. HtrA can therefore be considered a promising new target for anti‐bacterial therapy. Abstract : Bacterial pathogens depend on multiple proteases for various important tasks. This study shows that Helicobacter pylori serine protease HtrA is a bifunctional protein with crucial intracellular and extracellular activities. HtrA is preserved in sequence, evolution and E‐cadherin cleavage among worldwide isolates. HtrA inactivation is lethal, thus this is the first microbe in which htrA is an indispensable gene, a situation unique in the bacterial kingdom. HtrA is therefore a promising new target for antibacterial therapy.